2019
DOI: 10.1590/0103-6440201902086
|View full text |Cite
|
Sign up to set email alerts
|

Sensorial Ability, Mastication and Nutrition of Single-Implant Overdentures Wearers

Abstract: The use of two-implant overdentures improves mastication of edentulous elderly patients. However, little is known about the effects of single-implant overdentures (SIO) on oral perception and masticatory function in such elders. This study compared the effects of conventional complete dentures (CD) and SIO on the oral sensorimotor ability (OSA), masticatory function, and nutritional intake of elderly people with residual alveolar mandibular height classified as Class III or IV according to the American College… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
(47 reference statements)
0
25
0
Order By: Relevance
“…There were 2 prospective studies and 4 RCTs evaluating the masticatory function outcome of SIMO in different ways 24,25,27,28,38,39 . (Table 5) Two prospective studies confirmed better mastication efficiency after SIMO restoration 38,39 . A crossover RCT observed significantly higher mixing ability, comminuting ability and maximum bite force in SIMO group than in CCD group 24 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 2 prospective studies and 4 RCTs evaluating the masticatory function outcome of SIMO in different ways 24,25,27,28,38,39 . (Table 5) Two prospective studies confirmed better mastication efficiency after SIMO restoration 38,39 . A crossover RCT observed significantly higher mixing ability, comminuting ability and maximum bite force in SIMO group than in CCD group 24 .…”
Section: Resultsmentioning
confidence: 99%
“…There were 2 prospective studies and 4 RCTs evaluating the masticatory function outcome of SIMO in different ways. 24,25,27,28,38,39 ( a Group IC received a SIMO, whereas group CI received a CCD, for 2 mo; the treatments were interchanged for the next 2 mo.…”
Section: Masticatory Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have compared sodium intake between CD wearers and dentate individuals, thus making it difficult for us to interpret our results showing higher sodium intake in CD wearers than SIO wearers. One study showed lower sodium intake in SIO wearers, after 2 months of use than in CD wearers generally (baseline conditions), which was attributed to new SIO wearers improving their diet (ie, consuming foods with lower sodium). The major problem with elevated dietary sodium values is that high sodium intake increases the risk of coronary and circulatory diseases, particularly for older individuals who are already prone to renal diseases associated with a decline in physiological functions .…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the disadvantages of a removable prosthetic device, such as absence of retention and stability and the risk of malnutrition, given by the reduced nutrient absorption of a soft diet, dental implants have become the first‐choice for rehabilitating edentulous arches because implant‐supported prostheses improve one's ability to chew, essential for maintaining a proper diet, which in turn may prevent vitamin deficiencies and reduced nutrient intake, especially in older patients . To improve chewing ability for patients with resorbed ridges, a treatment approach involving a single implant overdenture (SIO) in the anterior midline region of the edentulous mandible has been described as a suitable, low‐cost alternative for patients who find it difficult to adapt to a lower CD.…”
Section: Introductionmentioning
confidence: 99%